### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0))), k(n(s(x), s(y)), s(s(0))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0, y) → 0
n(x, 0) → 0
n(s(x), s(y)) → s(n(x, y))
m(0, y) → y
m(x, 0) → x
m(s(x), s(y)) → s(m(x, y))
k(0, s(y)) → 0
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0, y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0) → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0) → true
f(s(x)) → h(x)
h(0) → false
h(s(x)) → f(x)
gt(s(x), 0) → true
gt(0, y) → false
gt(s(x), s(y)) → gt(x, y)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
n(s(x), s(y)) →+ s(n(x, y))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0].
The pumping substitution is [x / s(x), y / s(y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
g, f, k, minus, m, n, p, gt, h

They will be analysed ascendingly in the following order:
f < g
k < g
minus < g
m < g
n < g
f = h
minus < k
gt < p

### (8) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
minus, g, f, k, m, n, p, gt, h

They will be analysed ascendingly in the following order:
f < g
k < g
minus < g
m < g
n < g
f = h
minus < k
gt < p

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

Induction Base:
minus(gen_s:0':true:false2_0(0), gen_s:0':true:false2_0(0)) →RΩ(1)
gen_s:0':true:false2_0(0)

Induction Step:
minus(gen_s:0':true:false2_0(+(n4_0, 1)), gen_s:0':true:false2_0(+(n4_0, 1))) →RΩ(1)
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) →IH
gen_s:0':true:false2_0(0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
k, g, f, m, n, p, gt, h

They will be analysed ascendingly in the following order:
f < g
k < g
m < g
n < g
f = h
gt < p

### (12) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol k.

### (13) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
m, g, f, n, p, gt, h

They will be analysed ascendingly in the following order:
f < g
m < g
n < g
f = h
gt < p

### (14) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)

Induction Base:
m(gen_s:0':true:false2_0(0), gen_s:0':true:false2_0(0)) →RΩ(1)
gen_s:0':true:false2_0(0)

Induction Step:
m(gen_s:0':true:false2_0(+(n486_0, 1)), gen_s:0':true:false2_0(+(n486_0, 1))) →RΩ(1)
s(m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0))) →IH
s(gen_s:0':true:false2_0(c487_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (16) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
n, g, f, p, gt, h

They will be analysed ascendingly in the following order:
f < g
n < g
f = h
gt < p

### (17) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)

Induction Base:
n(gen_s:0':true:false2_0(0), gen_s:0':true:false2_0(0)) →RΩ(1)
0'

Induction Step:
n(gen_s:0':true:false2_0(+(n1036_0, 1)), gen_s:0':true:false2_0(+(n1036_0, 1))) →RΩ(1)
s(n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0))) →IH
s(gen_s:0':true:false2_0(c1037_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (19) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
gt, g, f, p, h

They will be analysed ascendingly in the following order:
f < g
f = h
gt < p

### (20) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)

Induction Base:
gt(gen_s:0':true:false2_0(+(1, 0)), gen_s:0':true:false2_0(0)) →RΩ(1)
true

Induction Step:
gt(gen_s:0':true:false2_0(+(1, +(n1484_0, 1))), gen_s:0':true:false2_0(+(n1484_0, 1))) →RΩ(1)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) →IH
true

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (22) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
p, g, f, h

They will be analysed ascendingly in the following order:
f < g
f = h

### (23) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol p.

### (24) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
h, g, f

They will be analysed ascendingly in the following order:
f < g
f = h

### (25) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
h(gen_s:0':true:false2_0(*(2, n2365_0))) → false, rt ∈ Ω(1 + n23650)

Induction Base:
h(gen_s:0':true:false2_0(*(2, 0))) →RΩ(1)
false

Induction Step:
h(gen_s:0':true:false2_0(*(2, +(n2365_0, 1)))) →RΩ(1)
f(gen_s:0':true:false2_0(+(1, *(2, n2365_0)))) →RΩ(1)
h(gen_s:0':true:false2_0(*(2, n2365_0))) →IH
false

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (27) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)
h(gen_s:0':true:false2_0(*(2, n2365_0))) → false, rt ∈ Ω(1 + n23650)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
f, g

They will be analysed ascendingly in the following order:
f < g
f = h

### (28) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol f.

### (29) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)
h(gen_s:0':true:false2_0(*(2, n2365_0))) → false, rt ∈ Ω(1 + n23650)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

The following defined symbols remain to be analysed:
g

### (30) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol g.

### (31) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)
h(gen_s:0':true:false2_0(*(2, n2365_0))) → false, rt ∈ Ω(1 + n23650)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

No more defined symbols left to analyse.

### (32) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

### (34) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)
h(gen_s:0':true:false2_0(*(2, n2365_0))) → false, rt ∈ Ω(1 + n23650)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

No more defined symbols left to analyse.

### (35) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

### (37) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)
gt(gen_s:0':true:false2_0(+(1, n1484_0)), gen_s:0':true:false2_0(n1484_0)) → true, rt ∈ Ω(1 + n14840)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

No more defined symbols left to analyse.

### (38) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

### (40) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)
n(gen_s:0':true:false2_0(n1036_0), gen_s:0':true:false2_0(n1036_0)) → gen_s:0':true:false2_0(n1036_0), rt ∈ Ω(1 + n10360)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

No more defined symbols left to analyse.

### (41) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

### (43) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)
m(gen_s:0':true:false2_0(n486_0), gen_s:0':true:false2_0(n486_0)) → gen_s:0':true:false2_0(n486_0), rt ∈ Ω(1 + n4860)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

No more defined symbols left to analyse.

### (44) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

### (46) Obligation:

TRS:
Rules:
g(s(x), s(y)) → if(and(f(s(x)), f(s(y))), t(g(k(minus(m(x, y), n(x, y)), s(s(0'))), k(n(s(x), s(y)), s(s(0'))))), g(minus(m(x, y), n(x, y)), n(s(x), s(y))))
n(0', y) → 0'
n(x, 0') → 0'
n(s(x), s(y)) → s(n(x, y))
m(0', y) → y
m(x, 0') → x
m(s(x), s(y)) → s(m(x, y))
k(0', s(y)) → 0'
k(s(x), s(y)) → s(k(minus(x, y), s(y)))
t(x) → p(x, x)
p(s(x), s(y)) → s(s(p(if(gt(x, y), x, y), if(not(gt(x, y)), id(x), id(y)))))
p(s(x), x) → p(if(gt(x, x), id(x), id(x)), s(x))
p(0', y) → y
p(id(x), s(y)) → s(p(x, if(gt(s(y), y), y, s(y))))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
id(x) → x
if(true, x, y) → x
if(false, x, y) → y
not(x) → if(x, false, true)
and(x, false) → false
and(true, true) → true
f(0') → true
f(s(x)) → h(x)
h(0') → false
h(s(x)) → f(x)
gt(s(x), 0') → true
gt(0', y) → false
gt(s(x), s(y)) → gt(x, y)

Types:
g :: s:0':true:false → s:0':true:false → s:0':true:false
s :: s:0':true:false → s:0':true:false
if :: s:0':true:false → s:0':true:false → s:0':true:false → s:0':true:false
and :: s:0':true:false → s:0':true:false → s:0':true:false
f :: s:0':true:false → s:0':true:false
t :: s:0':true:false → s:0':true:false
k :: s:0':true:false → s:0':true:false → s:0':true:false
minus :: s:0':true:false → s:0':true:false → s:0':true:false
m :: s:0':true:false → s:0':true:false → s:0':true:false
n :: s:0':true:false → s:0':true:false → s:0':true:false
0' :: s:0':true:false
p :: s:0':true:false → s:0':true:false → s:0':true:false
gt :: s:0':true:false → s:0':true:false → s:0':true:false
not :: s:0':true:false → s:0':true:false
id :: s:0':true:false → s:0':true:false
true :: s:0':true:false
false :: s:0':true:false
h :: s:0':true:false → s:0':true:false
hole_s:0':true:false1_0 :: s:0':true:false
gen_s:0':true:false2_0 :: Nat → s:0':true:false

Lemmas:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)

Generator Equations:
gen_s:0':true:false2_0(0) ⇔ 0'
gen_s:0':true:false2_0(+(x, 1)) ⇔ s(gen_s:0':true:false2_0(x))

No more defined symbols left to analyse.

### (47) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
minus(gen_s:0':true:false2_0(n4_0), gen_s:0':true:false2_0(n4_0)) → gen_s:0':true:false2_0(0), rt ∈ Ω(1 + n40)